Cholinesterase activities in the Antarctic scallop Adamussium colbecki: tissue expression and effect of ZnCl2 exposure - CORSI, I.; S. BONACCI; G. SANTOVITO; L. CASTAGNOLO; S. FOCARDI; CHIANTORE, MARIACHIARA (United Kingdom Kidlington Oxford: Elsevier Science Ltd, 2004)
Biochemical characterization of cholinesterase activity (ChE) was carried out on the Antarctic scallop Adamussium colbecki collected in winter 2000 from Campo Icaro (Ross Sea, Antarctica) in order to increase its suitability as a sentinel organism for monitoring the Antarctic environment. The digestive gland, gills and adductor muscle were investigated for substrate specificity and inhibitors sensitivity using acetylthiocholine iodide (ASCh) and butyrylthiocholine iodide (BSCh) as substrates and tetra (monoisopropyl)pyrophosphor-tetramide (Iso-OMPA), 1,5-bis(4-allyldimethylammoniumphenyl)-penthan-3-one dibromide (BW284c51) and the insecticide chlorpyrifos as inhibitors. Effect of in vivo exposure to ZnCl2 was also investigated. All the tissues expressed ChE activity (gill>adductor muscle>digestive gland) and low substrates specificity throughout the hydrolysis of both ASCh and BSCh substrates. Partial (25–29%) and total inhibition (100%) of ChE activity in gills was demonstrated following in vitro incubation with Iso-OMPA and BW284c51 (3 mM), respectively. Concentration-dependent inhibition was also evident with chlorpyrifos in the range 104–1010 M (IC50 106) while in vivo exposure to ZnCl2 did not seem to affect ChE activity in the scallop. The potential use of ChE in the A. colbecki as biomarker for monitoring water contamination in the marine Antarctic environment is discussed.